Air connection dropouts and isolation risks across European regions. Issue 3 (4th March 2022) - Manello, Alessandro; Scotti, Davide; Volta, Nicola
ABSTRACT: This work focuses on the duration of air connections in Europe and investigates the main factors affecting the probability that specific air routes survive over time. Socio-economic and geographical characteristics as well as modal competition, public subsidies and other airport/carrier-related factors are investigated. Moreover, we derive from our analysis the probabilities of connection dropouts to characterize European regions on the basis of their expected risks of increasing isolation. Our results might be of particular interest for policymakers and airport managers who intend to prevent their regions/airports from being affected by the negative consequences of increasing isolation. This is especially true in a context of expected increasing consolidation by major European network carriers.